Predicting Graduate Students’ Self-Efficacy for Thesis/Dissertation Completion in Sub-Saharan Africa - Millicent A Oyugi; Mathew Baker; Alexa J Lamm; Agnes Oywaya Nkurumwa Dr (Journal of International Agricultural and Extension Education, 2023)
Despite the global surge in enrollment for master's and Ph.D. programs worldwide and, to some extent, in Sub-Saharan Africa, a considerable lag in completing theses and dissertations (TD) persists. Personal, situational, and contextual factors, such as supervision arrangements and research abilities, have been correlated with the time taken for TD completion. However, beyond these variables, there remains a significant gap in our understanding of what precisely predicts TD completion. To contribute to this knowledge deficit, we conducted a study to determine the predictive nature of specific information sources on students' self-efficacy regarding TD completion. These sources encompass gender, graduate program level, coursework completion, prior statistical skills, and research knowledge. A survey built in Qualtrics was distributed to 65 masters and doctoral students in the Agricultural Education and Extension departments at four universities in Sub-Saharan Africa. The findings indicated that most respondents possessed prior experience with statistics or research and had completed their coursework. Nevertheless, self-reported research knowledge and self-efficacy for TD completion were rated average, signaling a clear need for proficient research skills to ensure punctual TD completion. Furthermore, hierarchical regression revealed that additional predictors, beyond research knowledge alone, led to a 42% increase in TD self-efficacy for completion. These findings suggest that graduate programs should prioritize providing students with more research-related mastery experiences. This could be accomplished by offering a broader range of statistical courses, hands-on research opportunities, and avenues for professional development. Additionally, institutions should evaluate to address the specific TD research requirements of graduate students through a gendered lens.
Keywords: dissertation-thesis completion; self-efficacy sources; agricultural education; graduate students; Africa; personal and contextual factors